2010
DOI: 10.2337/db09-0955
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion or Pharmacological Inhibition of Dipeptidyl Peptidase-4 Improves Cardiovascular Outcomes After Myocardial Infarction in Mice

Abstract: OBJECTIVEGlucagon-like peptide-1 (7-36)amide (GLP-1) is cleaved by dipeptidyl peptidase-4 (DPP-4) to GLP-1 (9-36)amide. We examined whether chemical inhibition or genetic elimination of DPP-4 activity affects cardiovascular function in normoglycemic and diabetic mice after experimental myocardial infarction.RESEARCH DESIGN AND METHODSCardiac structure and function was assessed by hemodynamic monitoring and echocardiography in DPP-4 knockout (Dpp4−/−) mice versus wild-type (Dpp4+/+) littermate controls and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(199 citation statements)
references
References 47 publications
10
179
0
2
Order By: Relevance
“…Taken together, similar trends with TG mice were observed in non-DM WT, WT-DM, and WT-DM-DPP4 inhibition groups, but these levels were low, and thus did not lead to decrease in infarct size in WT mice. Sauve et al reported that infarct size in genetic DPP4 deletion mice did not differ with that in WT mice, 37) and their data were consistent with our present study. In addition, Shigeta, et al reported that VEGF expression in cardiac muscle tissue was suppressed in the diabetic state with inhibition of DPP4 activity in a chronic heart failure model induced by transaortic constriction.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together, similar trends with TG mice were observed in non-DM WT, WT-DM, and WT-DM-DPP4 inhibition groups, but these levels were low, and thus did not lead to decrease in infarct size in WT mice. Sauve et al reported that infarct size in genetic DPP4 deletion mice did not differ with that in WT mice, 37) and their data were consistent with our present study. In addition, Shigeta, et al reported that VEGF expression in cardiac muscle tissue was suppressed in the diabetic state with inhibition of DPP4 activity in a chronic heart failure model induced by transaortic constriction.…”
Section: Discussionsupporting
confidence: 83%
“…Four weeks after the induction of MI by coronary ligation, the infarcted rat hearts were isolated and subjected to no treatment (vehicle), sitagliptin (5 μM), GIP (100 nM), GLP-1 (100 nM), or the combination of sitagliptin and GIP. The doses of sitagliptin, GIP and GLP-1 have been shown to be effective in modulating biological activities [25,26]. Noncirculating modified Tyrode's solution was used to perfuse each heart, containing glucose 5.5 mM, NaCl 117.0 mM, NaHCO 3 23.0 mM, KCl 4.6 mM, NaH 2 PO 4 0.8 mM, MgCl 2 1.0 mM and CaCl 2 2.0 mM, equilibrated at 37 • C with a 95 % O 2 and 5 % CO 2 gas mixture.…”
Section: Experiments 2 (Ex Vivo)mentioning
confidence: 99%
“…Dpp4 2/2 mice (Supplementary Fig. 1) were described previously (12); for doxorubicin experiments, n = 4-12 mice per group for vehicle controls and 9-12 mice per group for doxorubicin treatment. For TAC studies in Dpp4 +/+ vs. Dpp4 2/2 vs. mice, n = 6-7 per group.…”
Section: Animals Reagents and Dietsmentioning
confidence: 99%